Talukder Maniruzzaman’s Contribution to Political Studies in Bangladesh - Islam, Md Nazrul; Reza, S. M. Ali (Universitas Islam Internasional Indonesia (UIII), 2024)
Professor Talukder Maniruzzaman (1938-2019) was a noted Bangladeshi Muslim political scientist who breathed his last at a Dhaka hospital on December 29, 2019. Maniruzzaman was one of the few early Bangladeshi academics whose research in political science has significantly contributed to the discourse on political theory, governance, and state-society relations, especially within South Asia. This article aims to present and review his contribution to political science research in Bangladesh. Maniruzzaman’s studies largely investigated the interconnections of colonialism, nationalism, and post-colonial state frameworks in Bangladesh and adjacent areas. His thesis critically examined the influence of colonial legacies on the contemporary political scene, highlighting the enduring nature of authoritarian governance and socio-economic disparities originating from colonial control. Maniruzzaman was particularly recognized for his examination of political instability and state repression in post-independence South Asia, contending that the inadequacy of political institutions in newly-established governments frequently arises from the absence of inclusive state-building processes. In his key work, he critiqued the political structures in Bangladesh, highlighting the shortcomings of its political class and their inability to democratize the nation. Maniruzzaman’s work explored the interplay between political movements, national identity, and democratic ambitions. He contended that a genuinely democratic state must be established on the principles of social justice and equitable development. His comprehensive research substantially advanced the knowledge of the difficulties of political systems in post-colonial states and their pursuit of democratic consolidation.